The anomie of “smart drugs”: ethical controversies and responses to cognitive enhancers - Chen, Xiangyu (Acta Bioethica, 2025)
Cognitive Enhancers（CEs）have attracted considerable attention due to their capacity to enhance cognitive performance. These agents are classified into two categories: prescription drugs and non-prescription supplements. Despite their efficacy, the potential for addiction and associated risks have given rise to numerous ethical controversies. This article explores the ethical issues of using CEs, including fairness and equality, coercion and autonomy, health and safety risks, and social norms. It proposes that the ethical issues surrounding CEs should be addressed by implementing strict supervision, promoting informed consent, improving research transparency, and encouraging multi-stakeholder collaboration. These approaches aim to achieve a balance between bio-innovation and ethical responsibility.